2019
DOI: 10.1177/1055665619860038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postorthodontic Changes in the Treatment of Cleft Lip and Palate Patients Using the PAR Index

Abstract: Objective: To evaluate dental changes in cleft patients after undergoing orthodontic treatment for at least 2 years. Hypothesis: The dental change would decline significantly after 2 years of completing orthodontic treatment. Design: This is a retrospective study. Patient: Eighteen repaired cleft lip and palate patients from the Faculty of Dentistry, KhonKaen University, Thailand, participated in this study. Mean Outcome Measures: A dental model with before treatment (T0), completed treatment (T1), and retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…In the absence of a midpalatal suture posterior to the incisive foramen in patients with cUCLP, expansion prior to bone grafting only enhances the distance from the lesser segment to the nasal septum. Stability becomes an issue ( Marcusson & Paulin, 2004 ; Li & Lin, 2007 ; Trimetsuntorn et al, 2020 ), and inversion of the conventional treatment protocol with palatal expansion after bone grafting has been proposed, showing opening of the intermaxillary suture in the premaxilla in 43% of cases ( Da Silva Filho et al, 2009 , Garib et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a midpalatal suture posterior to the incisive foramen in patients with cUCLP, expansion prior to bone grafting only enhances the distance from the lesser segment to the nasal septum. Stability becomes an issue ( Marcusson & Paulin, 2004 ; Li & Lin, 2007 ; Trimetsuntorn et al, 2020 ), and inversion of the conventional treatment protocol with palatal expansion after bone grafting has been proposed, showing opening of the intermaxillary suture in the premaxilla in 43% of cases ( Da Silva Filho et al, 2009 , Garib et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in both of these studies, at the time of evaluation, there were several patients still needing maxillary osteotomies, meaning that the overall treatment had not yet been completed and thus final posttreatment occlusion could not be assessed. Few recent studies assessing posttreatment occlusion, including combined orthodontic/surgical cases, are available in the literature ( Marcusson & Paulin, 2004 ; Trimetsuntorn et al, 2020 ); nevertheless, the latter sample consisted of different cleft types with few participants in each subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…Mean PAR outcomes also do not account for this individual variation and may explain some of the differences in reported outcomes depending on the population from which the sample was drawn. A recent retrospective study of occlusal outcomes in 18 patients with CL/P found a mean reduction in PAR score of 29.33; however, this was higher in patients who underwent joint-orthognathic treatment, with a reduction of 32 (Trimetsuntorn et al, 2020). A similar study of 34 patients with UCLP found a mean PAR score reduction of 29.59, but a greater reduction of 37.43 for patients who underwent orthognathic correction (Manosudprasit et al, 2011).…”
Section: Outcome Comparisonsmentioning
confidence: 99%
“…The mean PAR reduction was 87% at completion of treatment, reducing to 73% after two years of retention. This negative change in PAR after treatment was found to be statistically significant (Trimetsuntorn et al, 2020). The later study also acknowledged that there was some overlap in the samples investigated in these studies.…”
Section: Introductionmentioning
confidence: 94%
“…An overall PAR reduction of 69% ± 22% was suggested as a benchmark for fixed appliance therapy in ULCP patients (Deacon et al, 2007). In two studies of cleft patients in Thailand, pre- and post-treatment PAR scores were also investigated (Manosudprasit et al, 2011, Trimetsuntorn et al, 2020). In the first of these studies, the records of 34 CLP patients, including seven who were treated with a joint orthodontic/orthognathic approach, were examined (Manosudprasit et al, 2011).…”
Section: Introductionmentioning
confidence: 99%